Pengaruh Penggunaan Abu Sekam dan Macam Pupuk Majemuk Terhadap Pertumbuhan dan Hasil Tanaman Tomat (Lycopersicum esculentum Mill) - Nidhar, Adien Naufal Abyan; Rusmarini , Umi Kusumastuti; Ardiani, Fani (J-Plantasimbiosa, 2024)
National food needs to focus on the agricultural sector. Tomato production in Indonesia is still low compared to other countries. This research aims to determine the impact of using husk ash and various types of compound fertilizers on the growth and yield of tomato plants. This study was conducted at KP2 INSTIPER Maguwoharjo, Special Region of Yogyakarta, in April-July 2023. This research used a Completely Randomized Design (CRD) composed of 2 factors. The first factor is the dose of husk ash, which consists of 3 levels, namely: 50g/polybag (control), 60g/polybag, and 70g/polybag; the second factor is the type of compound fertilizer, which consists of 3 types, namely; NPK 15:15:15, NPK 16:16:16, and NPK 9:25:25 at a dose of 10g/plant. Based on these two factors, 9 treatment combinations were obtained, each repeated 3 times, so there were 27 experimental plants. The research data was analyzed using variance with an actual level of 5%. The analysis results show an interaction between abusekam and compound fertilizer on the parameters of fruit diameter, average fruit weight, fresh shoot weight, and root fresh weight. Application of husk ash at a dose of 60g and NPK 15:15:15 gave a fruit diameter of 46.33 mm. Giving 70g of husk ash affects plant growth, fruit number, and fruit/plant weight. Providing NPK16:16:16 compound fertilizer has a good effect on plant growth, fruit number, and fruit/plant weight.